2010
DOI: 10.4178/epih/e2010008
|View full text |Cite
|
Sign up to set email alerts
|

Condom Use and Prevalence of Genital <italic>Chlamydia trachomatis</italic> Among the Korean Female Sex Workers

Abstract: OBJECTIVESSince 2004, availability of resources for preventing sexually transmitted diseases in Korean female sex workers (FSWs) has decreased because of strict application of a law against prostitution. This study is to evaluate the condom use and prevalence of Chlamydia trachomatis among FSWs in Korea.METHODSWe performed a cross-sectional study of FSWs from 15 major sex work sites in Korea from June to November 2008, using convenience sampling. Self-administered questionnaires and urine samples were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The results of the present study show that the risk factors for STD infections among FSWs in Republic of Korea are mainly related to working conditions. This is in part due to FSWs being coerced to provide services demanded by clients, with some FSWs practicing unprotected sex [11]. The present study reveals that the working conditions of FSWs, who are even more vulnerable today because of the provisions of the anti-prostitution act and the associated reductions to sex-traffic-related health budgets, are important factors associated with the incidences of STD infections.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The results of the present study show that the risk factors for STD infections among FSWs in Republic of Korea are mainly related to working conditions. This is in part due to FSWs being coerced to provide services demanded by clients, with some FSWs practicing unprotected sex [11]. The present study reveals that the working conditions of FSWs, who are even more vulnerable today because of the provisions of the anti-prostitution act and the associated reductions to sex-traffic-related health budgets, are important factors associated with the incidences of STD infections.…”
Section: Discussionmentioning
confidence: 87%
“…In 2006, an estimated 3.5% of the female adult urban population was engaged in commercial sexual transactions [10]. FSWs who live in urban areas have a particularly high risk of STD infections, including gonorrhea ( Neisseria gonorrhea ), syphilis ( Treponema pallidum ), and chlamydia ( Chlamydia trachomatis ) [11]. The poor working conditions experienced by FSWs can harm their sexual health and lead to psychological problems such as anxiety disorders, personality disorders, and depression [1214].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies were found in each of the following countries: England [ 116 , 117 ], New Zealand [ 118 , 119 ], Portugal [ 120 , 121 ] and Scotland [ 122 , 123 ]. One study was conducted in each of the following countries: Belgium [ 124 ], Chile [ 125 ], Czech Republic [ 126 ], Denmark [ 127 ], Estonia [ 128 ], Hungary [ 129 ], Panama [ 130 ], Puerto Rico [ 131 ], South Korea [ 132 ], and Switzerland [ 133 ]. Some studies were multi-jurisdictional for example Australian studies that compared three or more states [ 27 , 53 , 54 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The second largest group of studies were those which focused on locations where sex work was legal [ 48 , 49 , 51 , 52 , 59 , 60 , 61 , 64 , 100 , 103 , 104 , 106 , 107 , 125 , 126 , 129 , 130 , 133 ] followed by criminalized [ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 131 , 132 ]. Five studies were included where sex work was decriminalized [ 29 , 50 , 57 , 58 , 118 ] and one study was conducted in a setting with the Nordic model [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation